Green Technology Adoption and the Business Cycle - Jean-Marc Bourgeon; Margot Hovsepian (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze the adoption of green technology in a dynamic economy affected by random shocks where demand spillovers are the main driver of technological improvements. Firms' beliefs and consumers' anticipations drive the path of the economy. We derive the optimal policy of investment subsidy and the expected time and likelihood of reaching a targeted level of environmental quality under economic uncertainty. This allows us to estimate the value that should be given to the environment in order to avoid an environmental catastrophe as a function of the strength of spillover effects.
Keywords: E30; O30; O44; Q50; 330; growth; sustainability; uncertainty